1985
DOI: 10.1538/expanim1978.34.3_241
|View full text |Cite
|
Sign up to set email alerts
|

Serologic and Virologic Surveys on Feline Herpesvirus and Feline Calicivirus Infections in Cats for Experimental Use

Abstract: Both the antibodies in kittens were considered to be maternally derived. The FCV antibody rate was especially high in cats weighing 2.5 kg (males) and 2 .0 kg (females) or more, which were regarded as 8 to 10 months of age. An attempt was made to isolate the viruses from the oropharynx and conjunctiva of clinically healthy mature or immature cats and kittens.As the result, either one or both of the viruses were isolated from 31 of 75 mature and immature cats, and isolation rates of FHV and FCV were 6.7 % and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The diagnosis of FHV-1 infection is based on virus isolation with cell cultures, pathological findings, the direct fluorescent antibody test, polymerase chain reaction (PCR), real-time PCR, and serological assays (4,12,13). Virus neutralizing antibody titers measured with the virus neutralization assay are used to monitor sero-epidemiological status or to evaluate the immunogenicity of vaccination (14). Among the various diagnostic methods, virus isolation assesses the efficacy of trial feline vaccines and is used to establish serological diagnostic assays.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of FHV-1 infection is based on virus isolation with cell cultures, pathological findings, the direct fluorescent antibody test, polymerase chain reaction (PCR), real-time PCR, and serological assays (4,12,13). Virus neutralizing antibody titers measured with the virus neutralization assay are used to monitor sero-epidemiological status or to evaluate the immunogenicity of vaccination (14). Among the various diagnostic methods, virus isolation assesses the efficacy of trial feline vaccines and is used to establish serological diagnostic assays.…”
Section: Introductionmentioning
confidence: 99%
“…Seropositive rates of FHV-1 in advanced countries were reported to be relatively high [13,14,16,17]. However in Hanoi area, the positive rate of FHV-1 was extremely low and the virus seemed not to spread under a certain circumstance.…”
mentioning
confidence: 98%
“…Mixed vaccines against the viruses have been available in the countries and many cats have been vaccinated for prophylaxis. Epidemiological surveys against the viruses have been conducted in such advanced countries [2,7,[13][14][15][16][17], and the prevalence of the virus infections were seemed to be influenced by human customs for cats. In contrast, there are few reports for the prevalence of the viral diseases in developing countries where people seldom keep the cats as a companion animal and lack their interests to feline diseases although these countries would be proper fields to know the natural infection rates of these viruses.…”
mentioning
confidence: 99%
“…Earlier serological surveys showed that serum neutralizing antibody to FHV-1 is detectable in 50-75% of cat population [65,79]. In Japan, 20% of the sera of cats for experimental use were positive for FHV-1 antibodies [93].…”
Section: Hemagglutinin To Feline Red Blood Cell (Rbc)mentioning
confidence: 99%
“…The correlation between virus-neutralization (VN) and HA-inhibition (HI) antibodies in the sera from FHV-1-infected cats is demonstrated [55]. HI test can be used for a serological survey on FHV-1 infection in cats [93]. By solubilization of virus-infected cells with detergents, such as Triton X-100, sodium deoxycholate, or 3-[(3-cholamido-propyl) dimetyl-ammonio]-1-propanesulfinate (CHAPS), high titered hemagglutinins are successfully obtained [25].…”
Section: Hemagglutinin To Feline Red Blood Cell (Rbc)mentioning
confidence: 99%